Android Recipes A Problem-Solution Approach - Friesen, Jeff; Smith, Dave (Apress : Imprint: Apress, 2011)
Android continues to be one of the leading mobile OS and development platforms driving today's mobile innovations and the apps ecosystem. Android appears complex, but offers a variety of organized development kits to those coming into Android with differing programming language skill sets. Android Recipes: A Problem-Solution Approach guides you step-by-step through a wide range of useful topics using complete and real-world working code examples. In this book, you'll start off with a recap of Android architecture and app fundamentals, and then get down to business and build an app with Google's Android SDK at the command line and Eclipse. Next, you'll learn how to accomplish practical tasks pertaining to the user interface, communications with the cloud, device hardware, data persistence, communications between applications, and interacting with Android itself. Finally, you'll learn how to leverage various libraries and Scripting Layer for Android (SL4A) to help you perform tasks more quickly, how to use the Android NDK to boost app performance, and how to design apps for performance, responsiveness, seamlessness, and more. Instead of abstract descriptions of complex concepts, in Android Recipes, you'll find live code examples. When you start a new project, you can consider copying and pasting the code and configuration files from this book, then modifying them for your own customization needs. This can save you a great deal of work over creating a project from scratch!